Altruism and the Golden Rule - Goodman, Jonathan (Zygon, 2014)
This essay addresses recent claims about the compatibility of the sociobiological theory of reciprocal altruism with standard Western formulations of the Golden Rule. Derek Parfit claims that the theory of reciprocal altruism teaches us to be “reciprocal altruists,” who benefit only those people from whom we can reasonably expect benefits in the future. The Golden Rule, on the other hand, teaches us to benefit anyone regardless of their intention or ability to return the favor, or as Parfit puts it, the Golden Rule teaches us to be “suckers.” I argue that this distinction is founded on a misconception of the nature of the theory of reciprocal altruism, which is sociobiological as opposed to moral, and that this distinction accordingly confuses is with ought. Sociobiological theories may explain underlying psychological motivations in individuals (and perhaps even in populations), but these theories do not prescribe any sort of moral behavior. Furthermore, the theory of reciprocal altruism does not imply mental states of which agents are aware. The unconscious motivations assumed by this theory are in fact compatible with certain formulations of the Golden Rule; I will accordingly argue for the view that certain words with moral content related to the Golden Rule—such as “altruism” and “selfishness”—exist only insofar as they are social tools, which can further the self-interests of an individual in any group.